Catechin-based extract optimization obtained from Arbutus unedo L. fruits using maceration/microwave/ultrasound extraction techniques - Albuquerque, Bianca R. (2018)
This study compares three extraction techniques (maceration, microwave and ultrasound) for catechin recover from Arbutus unedo fruit extracts. To obtain the conditions that maximize catechin extraction yield, a response surface methodology was applied using a 3-level full factorial Box–Behnken design in which the processing time (t), temperature (T), ultrasonic power (W) and ethanol percentage (Et%) were the relevant independent variables with the response (catechin content, mg/g dw) measured by HPLC-PDA. A fixed solid/solvent ratio of 50 g/L was used in all techniques. Maceration and microwave extractions were found to be the most effective methods, capable of yielding 1.38 ± 0.1 and 1.70 ± 0.3 mg/g dw of catechin, respectively at the optimal extraction conditions. The optimal conditions for maceration were 93.2 ± 3.7 min, 79.6 ± 5.2 °C and 23.1 ± 3.7% of ethanol, while for the microwave extraction were 42.2 ± 4.1 min, 137.1 ± 8.1 °C and 12.1 ± 1.1% of ethanol. Comparatively with maceration, the microwave system was a faster solution, conducting to slightly higher catechin yields, but using higher temperatures to reach similar values. The ultrasound method was the least effective solution, yielding 0.71 ± 0.1 mg/g dw of catechin at 42.4 ± 3.6 min, 314.9 ± 21.2 W and 40.3 ± 3.8% ethanol. The results highlight the potential of using A. unedo fruits bio-residues as a productive source of catechin.